Natural history of the small snake Epictia munoai (Scolecophidia; Leptotyphlopidae): Reproductive cycle, sexual maturity and activity pattern - Mario-Da-Rosa, Conrado; Brum, Amanda J. C. [UNESP]; Loebens, Luiza; Santos, Tiago G.; Cechin, Sonia Z. (Wiley, 2025)
Epictia munoai is a small scolecophidian snake from the subtropical region of South America. It inhabits under rocks of preserved environments. Since basic information concerning the biology of this snake remains unknown, we aimed at presenting information on age, reproductive cycle, and daily and annual activity patterns of E. munoai from Southernmost Brazil. Males and females of E. munoai becomes sexually mature from 3 to 4 years of age, and presents a life expectancy of up to 9 or 10 years. The breeding cycle at the individual level is cyclical and discontinuous, and seasonal at the population level, with breed season from late winter to late spring. Epictia munoai is a diurnal snake, active under rocks during the hottest periods of the day, especially during the spring in southern latitudes. Our results provide new and unprecedented information about the natural history of a small species of South American fossorial snake. Information like this is extremely important as it helps to understand the life history of a species, in addition to serving as a basis for studies in areas such as population ecology, historical demography, phylogeography and conservation biology.
Keywords: longevity; reproductive cycle; skeletochronology; subtropical grasslands; temperature; yellow-blind-snake